Keberhasilan Pembangunan Pariwisata Berbasis Partisipasi Masyarakat (Studi Kasus Kelompok Sadar Wisata Nagari Lawang Kecamatan Matur Kabupaten Agam) - Indah Sari Rahmaini (Jurnal Pembangunan Nagari, 2022)
This study aimed to look at the polarization of development and community participation based on the Pokdarwis Nagari Lawang, sub-district of Matur, Agam district, West Sumatera. This research used qualitative method with case study type. Data was collected through observation, in-depth interview and Focus Group Discussion (FDG) The findings indicate that the success of Pokdarwis in carrying out participatory-based tourism development is due to good cooperation between Pokdarwis, the government, and nagari community. Pokdarwis as a facilitator in connecting the wishes of the community with the private sector, as well as the government as a supervisory and advisory agency in tourism development. Community involvement is not only in formal socialization, but Pokdarwis is also active in listening to the needs of the community through the lapau with the niniak-mamak of Nagari Lawang. The participation-based tourism development can be used as a guide for other regional Pokdarwis to build their tourism potential, namely by not forgetting the community as the main element of regional or nagari development.